Local Brand Adaptation Strategy: "Tiger Hood" In Bukittinggi - Fadila, Sindy; Suharti; Yetty Oktayanty (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research discusses "Local Brand” Adaptation Strategy: Tiger Hood in Bukittinggi. The purpose of this study is to describe the obstacles faced by the local brand Tiger Hood and how the adaptation strategy of the local brand Tiger Hood in Bukittingg. The theory used in this study is Tallcot Parson's theory of structural functionalism. The method used is a qualitative method with observation, interview, and documentation data collection techniques. The findings in this study explain that the local brand Tiger Hood has several obstacles in facing competition between fellow local brands in Bukittinggi such as fierce competition, changes in consumer preferences and consumer misperception. The adaptation strategies carried out by the local brand Tiger Hood such as promotions on social media, promos and discounts, improving product quality and improving customer service.